2020
DOI: 10.1177/0961203320967759
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of autoantibodies and cytokines related to cutaneous lupus erythematosus

Abstract: Objective To investigate the profiles of anti-RPLP0, anti-galectin3 antibodies, interferon-α (IFN-α), interferon-λ1(IFN-λ1) and interleukin-17A/F(IL-17A/F) in the subtypes of cutaneous lupus erythematosus (CLE) including acute CLE (ACLE), subacute CLE (SCLE) and discoid lupus erythematosus (DLE). Methods Serum levels of autoantibodies and cytokines were determined by enzyme-linked immunoabsorbent assay (ELISA). Lupus lesions were evaluated by cutaneous lupus erythematosus disease area and severity index (CLASI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, besides IL-17, Th-17 cells also produce IFN- λ1, and together these molecules provide protection from pathogens on the skin surface [ 77 ]. Several studies reported that the majority of SLE patients have increased levels of IL-17A and IL-17F [ 78 , 79 ].…”
Section: Il-12 Il-17 and Il-23mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, besides IL-17, Th-17 cells also produce IFN- λ1, and together these molecules provide protection from pathogens on the skin surface [ 77 ]. Several studies reported that the majority of SLE patients have increased levels of IL-17A and IL-17F [ 78 , 79 ].…”
Section: Il-12 Il-17 and Il-23mentioning
confidence: 99%
“…Levels of circulating IL-17A have been found to correlate with the Cutaneous Lupus Erythematosus activity and damage score index (CLASI) score [ 79 ], and high IL-17A expression has been demonstrated in the cellular infiltrates of the skin tissue of CLE lesions [ 80 ], as well as in kidneys affected by lupus nephritis (LN) [ 48 ]. High IL-17A levels at baseline predicted poor response to LN therapy [ 78 ] and deteriorating kidney function, if paralleled by INF-λ1 and IL-23 [ 18 ].…”
Section: Il-12 Il-17 and Il-23mentioning
confidence: 99%
“…IFNλ was expressed in barrier tissues, making it a crucial mediator of SLE-associated skin inflammation. Surprisingly, IFNλ was also involved in autoimmune inflammation at non-barrier sites, including the joints and kidneys [ 102 , 108 , 111 ]. These data suggest a potential role for T3IFN signaling in the development of B cell-driven autoimmunity, although the direct role of T3IFN signaling in autoimmune B cell responses in SLE remains poorly understood.…”
Section: Type 3 Interferon Signaling In Slementioning
confidence: 99%